Patologías comunes en lagomorfos durante la pasantía en una clínica veterinaria en Bogotá (2024)
When a non-conventional animal such as rabbits is acquired, often there is not enough information about their natural behavior and their respective care, this leads to the development of some diseases that can become life-threatening due to poor management by the guardians of these animals. Based on this, the present document seeks to create a manual for both the veterinarian and the owner on how to act in the face of these gastrointestinal pathologies.